2012
DOI: 10.1002/jobm.201100542
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and process parameter optimization of Brevibacterium casei for simultaneous bioremediation of hexavalent chromium and pentachlorophenol

Abstract: Chromate and pentachlorophenol are major pollutants discharged through tanneries. Three bacteria resistant to high Cr6+ and PCP concentrations simultaneously were isolated. The TVS‐3 strain was tolerant to highest 850 mg l−1 Cr6+ and 1000 mg l−1 PCP concentration and concomitantly reduced 69% Cr6+ and degraded 72% PCP within 168 h at pH 7.5, 35 ± 1°C temperature, was selected and identified as Brevibacterium casei. At 168 h of growth, bacterium showed maximum PCP utilization of 720 mg l−1 and released 900 mg l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 36 publications
1
15
0
Order By: Relevance
“…Interestingly, 82% degradation of the organic compound with simultaneous Cr 6+ reduction was reported, unlike in the present study where about 50% of the PHs were degraded along with sequestration the Ni 2+ and Co 2+ within the same time frame. It is noteworthy that PHs are more hydrophobic and recalcitrant than phenolic compounds, and this might be responsible for the lower degradation observed in the bacterial strains than the findings of Verma and Singh . Apparently, 5.0 mM is not toxic enough to impede metabolic potential of the strains investigated, and thus incapable of retarding degradation of the PHs.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Interestingly, 82% degradation of the organic compound with simultaneous Cr 6+ reduction was reported, unlike in the present study where about 50% of the PHs were degraded along with sequestration the Ni 2+ and Co 2+ within the same time frame. It is noteworthy that PHs are more hydrophobic and recalcitrant than phenolic compounds, and this might be responsible for the lower degradation observed in the bacterial strains than the findings of Verma and Singh . Apparently, 5.0 mM is not toxic enough to impede metabolic potential of the strains investigated, and thus incapable of retarding degradation of the PHs.…”
Section: Discussionmentioning
confidence: 71%
“… demonstrated that low concentrations of Zn 2+ and Mn 2+ (1–10 mg l −1 ) stimulated biomass growth of Ochrobactrum cytisi on tert ‐butyl ether, unlike Ni 2+ (1–4 mg l −1 ) that retarded the growth. Moreover, Brevibacterium casei was reportedly reduced 78% Cr 6+ along with 82% degradation of pentachlorophenol simultaneously . In the contrary, Ni has been found to inhibit bacterial utilization of PHs in contaminated soils .…”
Section: Discussionmentioning
confidence: 99%
“…Similarly at 200 rpm, complete phenol removal and up to 78% removal of Cr (VI) were detected at 96 h of treatment. Verma and Singh (2013) have observed increased reduction of pentachlorophenol and Cr (VI) with increased in agitation speed up to 120 rpm using Brevibacterium casei. However, the authors reported lower reduction of contaminants with further increase in agitation speed which is contrary to our findings.…”
Section: Effect Of Varying Agitation Speed On Concomitant Removal Of mentioning
confidence: 90%
“…have been earlier used for the treatment of metal contaminated waste. However, these treatments are very expensive, require large amount of chemical and energy, produce secondary waste into the environment and affect soil texture (Szpyrkowicz et al, 2001;Verma and Singh, 2013). Bacteria show potential approach in this regard as they could adapt and inhabit such polluted environments and remediate the toxic metals by converting them into less toxic and easily disposable forms.…”
Section: …………………………………………………………………………………………………… Introduction:-mentioning
confidence: 99%